THE EFFECTIVENESS OF GROUP COUNSELING SERVICES WITH SELF DISCLOSURE TECHNIQUES TO REDUCE PSYCHOLOGICAL BULLYING BEHAVIOR - Cut Tarisa; Saiful Akhyar Lubis (LP2M IAI Al-Khairat Pamekasan, 2025)
Psychological Bullying behavior that occurs in schools includes: isolating friends, ignoring, looking at them cynically and insulting their friends. This study aims to determine the effectiveness of group counseling services with the Self Disclosure technique in reducing Psychological Bullying Behavior in students of SMA N 1 Sunggal. The method used is quantitative with a One Group Pretest-Postest research design. The sample consisted of 9 students who showed indications of high to moderate Psychological Bullying behavior. Data collected through questionnaires, interviews and documentation. The results of the Wilcoxon test showed a significant value of 0,008<0,05, which means there is a significant difference between the pretest-posttest scores. These results indicate that group counseling services with the Self Disclosure technique are effective in reducing Psychological Bullying behavior.